A new fluorescent probe for specific detection of cysteine with facile preparation and living cell imaging. (July 2019) - Chen, Dugang; Long, Zi; Dang, Yecheng; Chen, Li
Abstract: The detection of cysteine (Cys) is of great significance ascribed to its important role in physiological and psychological process. This paper reported a new fluorescent probeCBFA with red emission signal, which can be prepared through a simple method and exhibited potential application value. Solution experiments demonstrated that the probe revealed high selectivity towards Cys in spite of the interference of its two analogues, homocysteine (Hcy) and glutathione (GSH). And the sensitivity indicated that the probe was suitable for Cys detection in living cells. Furthermore, the recognition mechanism was confirmed to be a concerted reaction including Michael addition and intramolecular cyclization by high resolution mass spectrometer (HRMS) and high-performance liquid chromatography (HPLC). Besides, CBFA showed favorable pH adaptability in biological conditions and low cytotoxicity. Finally, CBFA was successfully applied to selectively imaging Cys in living MCF-7 cells with good cell permeability. We hope this probe will bring some help to the diagnosis of Cys-related diseases. Graphical abstract: Image 1 Highlights: A new fluorescent probe for cysteine detection with red emission signal. Preparing process of the probe was rather simple. Sensitivity of the probe was satisfactory for Cys detection in living cells. Endogenous Cys imaging in living cells with high selectivity and sensitivity.